1984
DOI: 10.1113/jphysiol.1984.sp015151
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by papaverine of calcium movements and tension in the smooth muscles of rat vas deferens and urinary bladder.

Abstract: SUMMARY1. Papaverine, up to 150 /M, was without effect on resting tension of vas deferens and urinary bladder smooth muscle strips, but caused a dose-dependent inhibition of the phasic component of the 100 mM-K contracture. At 150 FM, papaverine caused an 80 and 60 % inhibition ofphasic tension in vas deferens and urinary bladder muscle respectively.2. Papaverine caused a marked dose-dependent reduction in the tonic component of 100 mM-K contractures in both preparations. At 150 /M, papaverine often relaxed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…Electrophysiological studies showed that papaverine, irrespective of the level of cyclic AMP, inhibits VOCs to cause relaxation of the dog basilar artery. In other electrophysiological studies (Itoh et al, 1981;Brading et al, 1983) and 45Ca2l studies (Huddart et al, 1984), papaverine seemed to inhibit Ca2l influx as a means of causing relaxation of smooth muscle.…”
Section: Inhibition Of Ca`influxmentioning
confidence: 99%
“…Electrophysiological studies showed that papaverine, irrespective of the level of cyclic AMP, inhibits VOCs to cause relaxation of the dog basilar artery. In other electrophysiological studies (Itoh et al, 1981;Brading et al, 1983) and 45Ca2l studies (Huddart et al, 1984), papaverine seemed to inhibit Ca2l influx as a means of causing relaxation of smooth muscle.…”
Section: Inhibition Of Ca`influxmentioning
confidence: 99%
“…It blocks the contractile response to excitatory agents (Tashiro and Tomita, 1970;Brading et al, 1983;Huddart et al, 1984). Because of those relaxant effects on smooth muscles, papaverine has been used as a vasodilator agent (Wilson and White, 1986;Franz et al, 1991;Newell et al, 1999) and as a therapeutic agent for renal colic (Jonsson et al, 1987) and penile impotence (Handelsman, 1990).…”
mentioning
confidence: 99%
“…Furthermore, the opposite effects of aminophylline and of CBZ cancelled each other when effective doses of the two drugs were combined. However, because papaverine is known to yield other neuronal effects besides those on the adenosinergic system (Triner et al 1970;Huddart et al 1984;O'Hara and Ono 1987), and the above behavioural antagonism could be due to interference with different functionally opposed neuronal systems, additional experimental evidence is necessary to test the adenosine hypothesis of CBZ anxiolytic action.…”
Section: Anxiogenic Effect Of Aminophyllinementioning
confidence: 97%